An increased susceptibility of Staphylococcus aureus to tetracyclin during exposure to rifampicin - Hera Nirwati, Hera Nirwati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1998)
acterial resistance to antibiotics has been an important problem worldwide. Discoveries and clinical use of new antibiotics have always been followed by emergence of strains of bacterial resistant to the antibiotics in question within relatively short period of time. Various efforts have been attempted to overcome the problem, one of which being the use of two or more different antibiotics in combination. In this study the effect of rifampicin on alternation of susceptibility of S. aureus to tetracycline was evaluated. Sixty seven isolates of tetracycline resistant S. aureus determined by standard disk diffusion method of Kirby-Bauer were collected during the period from August 1997 to January 1998. Minimal Inhibitory Concentration (MIC = KHM) values of rifampicin for this isolates were determined by broth dilution method. MIC of tetracycline for each isolate was determined while the bacteria were exposed to rifampicin at sub MIC. At the same time determination of the MIC was also performed without exposing the bacteria to rifampicin and this procedure served as control. Results showed that 91% (61 of 67) rifampicin - exposed isolates have increase susceptibility to tetracycline as reflected by the decrease of MIC values. It is concluded that there is synergistic effects of tetracycline and rifampicin on S. aureus. The number of isolate with increased susceptibility to tetracycline during exposure to rifampicin was statistically significant (p < 0.05).Key Words : rifampicin - Staphylococcus aureus - susceptibility - tetracycline